Examining the Impact of Social Pressure on Golf Putting Performance - Kingsbury, Adam (Université d'Ottawa / University of Ottawa, 2020)
Fine-motor skills in any domain (e.g., sports, surgery, music) are subject to performance decrements under pressure. A large majority of studies that have examined “choking under pressure” used golf putting as a paradigm to test participants. Golf putting is a fine-motor skill that is highly susceptible to deviations in performance, yet a skill that appears to be deceptively simple without a steep learning curve. The following thesis contained three studies that examined the influence of social evaluative threat on the objective outcome performance (holed or not holed, distance to the hole), as well as the kinematic variables associated with the putting stroke itself. Performance was measured using a high-speed infrared camera called the TOMI® which collected real-time 3D data about a number of different kinematic parameters for each putt that was struck. While it was expected that a learning effect would characterize the longitudinal trajectory of performance, it was also expected that state anxiety would moderate this trajectory. In Study 1, 35 amateur golfers, completed a self-report measure of state anxiety and performed golf putting tasks under a neutral condition followed by a social-evaluative condition. Somatic anxiety was related to differential performance trajectories, while cognitive anxiety was associated with variability in the backstroke. In Study 2, 27 beginner participants participated in an improved design based on Study 1. Somatic anxiety temporarily moderated performance under pressure for the novices. In Study 3, 55 beginner participants were recruited and randomized to either a stress-free learning task (n = 29), or a social-evaluative learning task (n = 26), to address research limitations from the first two studies. Furthermore, methodological concerns present in both Study 1 and 2 were addressed, with the aim of contributing to the debate surrounding theoretical mechanisms of how performance decrements occur, specifically under social-evaluative threat. High levels of somatic anxiety moderated the objective performance trajectory of the experimental group, and surprisingly decreased the amount of time taken to prepare for each putt in the social-evaluative task. In all three studies, somatic anxiety significantly moderated both objective and indirect performance (as indicated by kinematics and routine time). Taken together, these studies suggest that one’s interpretation of physiological symptoms while under social evaluative threat can temporarily impair performance trajectories of a fine-motor skill.
Keywords: Golf Putting; State Anxiety; Social Evaluative Threat; Sport Psychology